The dependence on intracellular ATP concentration of ATP-sensitive K-channels and of Na,K-ATPase in intact HIT-T15 beta-cells. - Niki, I; Ashcroft, F; Ashcroft, S (1989)
We have studied the effects of changes of intracellular ATP concentration ([ATP]i) on the activity of ATP-sensitive K-channels (IK(ATP] and of Na,K-ATPase in intact cells of the insulin-secreting cell-line HIT-T15. Pre-exposure of HIT beta-cells to oligomycin caused a dose-dependent reduction in [ATP]i. Marked activation of IK(ATP) activity was found when ATP was lowered below 3 mM. Na,K-ATPase was progressively inhibited as ATP was lowered to 1.5 mM. These data demonstrate that changes in intracellular ATP in the millimolar range markedly influence the activity of two beta-cell membrane proteins having affinities for ATP in the micromolar range. This suggests that submembrane [ATP] may be considerably below the measured bulk cytosolic concentration. The findings also support the proposed role of intracellular ATP in mediating effects of changes in glucose concentration on the activity of beta-cell IK(ATP) and insulin secretion.